A radial basis function (RBF) finite difference method for the simulation of reaction–diffusion equations on stationary platelets within the augmented forcing method. (29th January 2014) - Shankar, Varun; Wright, Grady B.; Fogelson, Aaron L.; Kirby, Robert M.
SUMMARY We present a computational method for solving the coupled problem of chemical transport in a fluid (blood) with binding/unbinding of the chemical to/from cellular (platelet) surfaces in contact with the fluid, and with transport of the chemical on the cellular surfaces. The overall framework is the augmented forcing point method (AFM) (L. Yao and A.L. Fogelson, Simulations of chemical transport and reaction in a suspension of cells I: An augmented forcing point method for the stationary case, IJNMF (2012) 69, 1736–52.) for solving fluid‐phase transport in a region outside of a collection of cells suspended in the fluid. We introduce a novel radial basis function–finite difference (RBF‐FD) method to solve reaction–diffusion equations on the surface of each of a collection of 2D stationary platelets suspended in blood. Parametric RBFs are used to represent the geometry of the platelets and give accurate geometric information needed for the RBF‐FD method. Symmetric Hermite‐RBF interpolants are used for enforcing the boundary conditions on the fluid‐phase chemical concentration, and their use removes a significant limitation of the original AFM. The efficacy of the new methods is shown through a series of numerical experiments; in particular, second‐order convergence for the coupled problem is demonstrated. Copyright © 2014 John Wiley & Sons, Ltd.